THE METHODOLOGY OF REGIONAL LEVEL ASSESSMENT IN INSTITUTIONAL DEVELOPMENT OF THE RETAIL TRADE - О. Є. Мазур (Ринкова економіка: сучасна теорія і практика управління)
Interregional differentiations in trade business development of any country are an objective and natural phenomenon. However, if they are getting excessive, it creates a basis for the productive forces decline especially in individual regions and reduces living standards for local population. This tendency had identified a need for the regional asymmetry level assessment in retail trade development of Ukraine. A review of the scientific studies indicates that there are no fundamental analytical studies of institutional aspect assessment of the retail trade: scientists basically compare regions using economic and technological indicators of the trade. The paper has developed a methodology in institutional development assessment of the retail trade at a regional level. The synthesis rate was introduced into the scientific circulation - the index of institutional development in the retail trade. It was based on philosophical ideas about the development process which is characterized by transformations of structure behavior, and rates of change. It has been developed an algorithm for the index calculation. Methodological approaches which help to understand definition of its components was also created. Methods of grouping, comparison, integral indicators, standardization (normalization) indicators, peer review, graphical methods were used as the methods for the analysis of institutional development in the trade. The retail trade level in Ukrainian regions in 2012 was used as a basis for calculations. The presented method allows calculating the generalized indicator in order to take into account the complex of the components that characterize various aspects of trade development as a socio-economic institute of the modern economy. It had become possible to identify weaknesses and winning positions in components of institutional trade development.